Body’s movement as drawing: notation and annotation in the construction of space at alun-alun solo - Defry Agatha Ardianta; Yandi Andri Yatmo; Paramita Atmodiwirjo (Penerbit Universiti Kebangsaan Malaysia, 2023)
This paper will discuss the study of space quality by reading the body’s movement as drawing. The understanding of notation on drawing thinking is used to read the spatial function arrangement in alun-alun, a public open space found in many cities in Indonesia, where there are no solid spatial boundaries. Alun-alun is a public space related to socio-cultural aspects and has a complex layer of events. A certain reading method is needed to reveal the quality of the space, and not only read one layer of conditions. The understanding of notation is used because notational characters beyond visual have time variables and social contexts, opening up the possibility of shared interpretations. The study was conducted at Alun-alun Solo, Central Java, by placing the activity and movement of visitors as an essential element that is present along with the arrangement of spatial functions determined by street vendors and playgrounds. This study was conducted using mapping the notational structure of spaces and tracing the movement of visitors over the spatial arrangement. The findings in this study are the presence of multiple annotations that overlap the defined space. The annotation in the drawing thinking process shows that conditions are considered unfinished, still in progress, and there are simultaneous thought processes in action. The existence of annotations from the visitor’s body movement reveals the significance of forming a different quality of space, which is constructed from everyday phenomena and does not depend on the arrangement of the notation that has been determined.